Bahasa Inggris - Pradipa, I Gede Yogi Lingga; Tammubua, Jerroll Septian; Lestari, Putu Masayu Cahyaning; Rindawan, Made Yuda; Wiguna, I Made Bagus Krishna (Essence of Scientific Medical Journal; Vol 22 No 2 (2025): Volume 22 No. 2 (November 2024 - Maret 2025) Essential: Essence of Scientific Medical JournalDO - 10.24843/essential.v22i2.121517, 2025)
Introduction: Leptospirosis is a globally widespread zoonotic infection caused by the bacterium “Leptospira”, particularly common in tropical regions and can cause large-scale epidemics following floods or heavy rains. Primarily, the management of leptospirosis will use antibiotics such as penicillins, ampicillin, amoxicillin, or doxycycline. The management of giving antibiotics with higher doses to leptospirosis patients also creates the possibility of antibiotic resistance which causes the bacteria to become resistant to the effects of antibiotics.  This study aspires to ensure better patient outcomes and more efficient medical interventions. This research uses a systematic literature review method, which uses research articles related to the topic based on the PICO method with The inclusion criteria used were articles published between 2019-2024 range, were fully accessible, relevant to keywords and also written in Indonesian and English. Discussion: From the search results for journal articles, it was found that it consists of brief descriptions of resistance and changes in function of several antibiotics like ?-lactams, cephalosporins, doxycycline, ciprofloxacin, fluoroquinolones, nalidixic acid, penicillin, streptomycin, and ampicillin in leptospirosis. These studies also highlight the association with antibiotic resistance in Leptospira and emphasize the need for continued monitoring to reduce the increase in antibiotic resistance in leptospirosis. Conclusion : The research emphasizes the growing concern of antibiotic resistance in Leptospira species, with genetic factors and mechanisms like efflux pumps complicating treatment outcomes and highlighting the need for ongoing surveillance and more effective treatment strategies.